Notes on the lectotype of Tetrapogon roxburghianus (Poaceae: Chloridoideae: Cynodonteae) - Das, Shrabasti; Karthigeyan, Kaliyamurthy (Phytotaxa, 2020)
Tetrapogon Desfontaines (1799: 388) comprises 10 species distributed in warmer parts of Africa, Middle East, India, Pakistan, Mexico and Cuba (Mabberley 2018, Soreng et al. 2017). The genus is represented in India by three species namely Tetrapogon roxburghianus (Schultes) P.M.Peterson in Peterson et al. (2015: 460), T. tenellus (J. Koenig ex Roxburgh 1814: 82) Chiovenda (1908: 352) and T. villosus Desfontaines (1799: 389).